2023
DOI: 10.1038/s42255-023-00828-5
|View full text |Cite|
|
Sign up to set email alerts
|

Commensal bacteria weaken the intestinal barrier by suppressing epithelial neuropilin-1 and Hedgehog signaling

Abstract: The gut microbiota influences intestinal barrier integrity through mechanisms that are incompletely understood. Here we show that the commensal microbiota weakens the intestinal barrier by suppressing epithelial neuropilin-1 (NRP1) and Hedgehog (Hh) signaling. Microbial colonization of germ-free mice dampens signaling of the intestinal Hh pathway through epithelial Toll-like receptor (TLR)-2, resulting in decreased epithelial NRP1 protein levels. Following activation via TLR2/TLR6, epithelial NRP1, a positive-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
1
10
0
1
Order By: Relevance
“…NRP1 deficiency in visceral smooth muscle cells could negatively impact GI contractility and motility 326 . Also, the viral hijack-mediated suppression of epithelial NRP1 could weaken the gut barrier function 327 . The NRP-1-mediated SARS‐CoV‐2 entry into bone marrow‐derived macrophages (BMM) could impede osteoclast differentiation and affect calcium/phosphorus metabolism in COVID‐19 patients 328 .…”
Section: Pasc: Viral-hijacked Host Cellular Factors and Consequencesmentioning
confidence: 99%
“…NRP1 deficiency in visceral smooth muscle cells could negatively impact GI contractility and motility 326 . Also, the viral hijack-mediated suppression of epithelial NRP1 could weaken the gut barrier function 327 . The NRP-1-mediated SARS‐CoV‐2 entry into bone marrow‐derived macrophages (BMM) could impede osteoclast differentiation and affect calcium/phosphorus metabolism in COVID‐19 patients 328 .…”
Section: Pasc: Viral-hijacked Host Cellular Factors and Consequencesmentioning
confidence: 99%
“…Growing evidence demonstrated that gut microbiota not only provide essential capacities for the metabolism of nutrients, but also participate in regulating the integrity and function of the intestinal barrier in a homeostatic balance ( 68 , 69 ). Therefore, gut microbiota homeostasis is vital for intestinal barrier integrity and the underlying mechanism are largely unknown ( 70–72 ). Gut microbiota provide essential capacities for the fermentation of non-digestible substrates like dietary fibers and endogenous intestinal endogenous intestinal mucus ( 73 ).…”
Section: Effects Of Astragalus Polysaccharide On Intestinal Barriermentioning
confidence: 99%
“…Also, GM suppresses tonic Hedgehog (Hh) signaling in the small intestine, thus regulating intestinal barrier function. Hh pathway activity is mainly suppressed through Toll-like receptor (TLR2/TLR6) signaling in the intestinal epithelium, identifying intestinal epithelial neuropilin-1 (NRP1) as a microbiota-dependent Hh regulator that contributes to the stabilization of the intestinal epithelium barrier [40] .…”
Section: Purpose Of Using Germ-free Animal Modelsmentioning
confidence: 99%